2003
DOI: 10.1063/1.1565693
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-doping of rutile-titanium dioxide by ion implantation: Photocurrent spectroscopy and first-principles band calculation studies

Abstract: Sulfur (S)-doped titanium dioxide (TiO2) was synthesized by ion implantation and subsequent thermal annealing. The S ions were implanted into the single crystals of rutile TiO2 at a fluence of 8×1015 ions/cm2. According to the results of Rutherford backscattering spectroscopy and ion channeling analysis, the irradiation damage recovered by annealing at 600 °C in air. In the annealed crystal, the S atoms occupied oxygen sites for form Ti-S bonds, as confirmed by x-ray photoelectron spectroscopy. Compared to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
223
4
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(239 citation statements)
references
References 30 publications
11
223
4
1
Order By: Relevance
“…106 Yuan et al found that in nitrogen (N)-doped TiO 2 samples the N was presented in the state of both molecularly chemisorbed N 2 and substituted N; while both of them contributed to the response to visible light, the substituted N was responsible for the hydrogen evolution under visible light. 110 S dopant induced a similar bandgap narrowing as nitrogen: 89 the mixing of the sulfur 3p states with the valence band was found to contribute to the increased width of the valence band, leading to the narrowing of the bandgap, 91,93 the strong absorption in the region from 400 to 600 nm. 99 In Asahi's study, C dopant introduced deep states in the gap.…”
mentioning
confidence: 91%
“…106 Yuan et al found that in nitrogen (N)-doped TiO 2 samples the N was presented in the state of both molecularly chemisorbed N 2 and substituted N; while both of them contributed to the response to visible light, the substituted N was responsible for the hydrogen evolution under visible light. 110 S dopant induced a similar bandgap narrowing as nitrogen: 89 the mixing of the sulfur 3p states with the valence band was found to contribute to the increased width of the valence band, leading to the narrowing of the bandgap, 91,93 the strong absorption in the region from 400 to 600 nm. 99 In Asahi's study, C dopant introduced deep states in the gap.…”
mentioning
confidence: 91%
“…20,21 Recent literature reports indicate that sulphur could either add to the TiO 2 matrix as a cation or an anion depending upon the sulphur source employed. [22][23][24][25][26][27] Umebayashi et al…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] This anion doping shifts the absorption spectrum of titania to a lower energy and effectively leads to visible light activity. Ohno It should also be noted that upon 10 wt% addition of CuSO 4 , copper segregated as bonattite (CuSO 4 ·3H 2 O) after annealing the sample at 400 °C or lower temperature and as antierite (Cu 3 SO 4 (OH) 4 ) after annealing the sample at 800 °C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Enhanced photocatalysis is seen when TiO 2 is doped with some elements, such as C, N, and F, which are claimed to substitute for O in the bulk, and S doping may have similar effects. [6][7][8][9][10][11] On the other hand, S impurities are known to inhibit photocatalytic reactions, so unwanted S impurities might limit photocatalytic performance.…”
mentioning
confidence: 99%